The role of the antioxidant ascorbic acid in the elicitation of contact allergic reactions to p‐phenylenediamine. (15th February 2016) - Coenraads, Pieter‐Jan; Vogel, Tatiana A.; Blömeke, Brunhilde; Goebel, Carsten; Roggeband, Robert; Schuttelaar, M.L.A.
Summary: Background: An allergic contact reaction is accompanied by high oxidative stress in the skin. Pretreatment of the skin with antioxidative substances could reduce the elicitation reaction. Objectives: To investigate, in a proof‐of‐principle study, whether pretreatment of the skin with the antioxidant ascorbic acid reduces the elicitation reaction to a p ‐phenylenediamine (PPD)‐containing hair dye in sensitized subjects. Methods: Twelve subjects with contact allergy to PPD, a documented skin reaction to a hair dye simulation exposure model and a history of hair dye‐related skin complaints were included in this study. Skin areas on the forearms were, in a left versus right design, exposed to an emulsion with ascorbic acid and an emulsion without ascorbic acid, and then to a 2% PPD‐containing hair dye testing formulation. In addition, control areas were exposed to the emulsions and to the PPD‐containing hair dye formulation without pretreatment. Skin reactions were graded on day (D)2 and D3. Results: Pretreatment with ascorbic acid emulsion resulted in a reduction in the elicitation reaction in 7 of 12 subjects at D3 ( p = 0.046). No statistically significant difference was observed at D2. Conclusions: Pretreatment of the skin with the antioxidant ascorbic acid had an attenuating effect on the elicitation reaction to PPD in sensitized individuals.